Przewodniczący Rady Europejskiej – między strategią polityczną a rutyną pracy urzędnika - PRZYBYLSKA-MASZNER, BEATA (Rocznik Integracji Europejskiej, 2012)
Following the changes introduced by the Lisbon Treaty, the European Council elects its permanent president by a qualified majority. The first President of the European Council developed his office on his own, watched by those whose expectations envisaged him performing various tasks, such as leader, political strategist, broker, or just another EU official. The Treaty did not precisely define the range of powers conferred upon the President of the European Council but it provided a stimulus to start the adaptation of this new position to specific tasks. There is emerging a new, post-Lisbon practice of the new institutional system’s operation, as well as the new form of the European Council, with a key role played by its President. The objective of this paper is to present the circumstances under which the office of President of the European Council was established, as well as an analysis of the scope of his responsibilities. These considerations are concluded with the evaluation of the theoretical and practical powers exercised by the President of the European Council during the first, and at the beginning of the second term.